Peran Pendidikan Islam dalam Membentuk Perubahan Sosial pada Anak Sekolah Dasar: Perspektif Sosiologi Pendidikan Islam - Zainal Arifin; Muzakki; Ghofari (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Education plays a strategic role in shaping individuals and directing social change, particularly at the elementary education level as the foundational stage of children’s character development. From the perspective of Islamic sociology of education, education does not merely function as a means of transferring knowledge, but also serves as an instrument for internalizing Islamic, moral, and social values that influence behavioral changes at both individual and societal levels. This study aims to analyze the influence of education on social change among elementary school children by highlighting the role of schools, teachers, and the Islamic educational environment in shaping social awareness, character, and patterns of interaction. The research employs a literature review method with a qualitative-descriptive approach through the analysis of various relevant academic journals and books. The findings indicate that value-based Islamic education is able to promote positive social change in children, such as increased discipline, responsibility, social awareness, and adaptability to societal changes. Therefore, Islamic education at the elementary school level has a significant contribution in forming a generation that is morally grounded, knowledgeable, and actively engaged in social change within society.